Current in vitro assay to determine bacterial biofilm formation of clinical isolates - Titik Nuryastuti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2014)
Biofilm mode of growth is bacterial lifestyle widespread in microbial world and represents a concernin health care. Recently, serious problem concerning biofilm-related infection is increasing significantly.However complexity of biofilm makes it difficult to conduct proper analysis. Although biofilm representsa major challenge for microbiologist, methods aimed to determine biofilm formation and developmentare not standardized yet. The aim of the present review was to provide an overview of the advantagesand disadvantages of the difference in vitro methods for determining biofilm forming ability ofclinical isolates.